Cleavage of the main carbon chain backbone of high molecular weight polyacrylamide by aerobic and anaerobic biological treatment. (December 2017) - Song, Wenzhe; Zhang, Yu; Gao, Yingxin; Chen, Dong; Yang, Min
Abstract: High molecular weight partially hydrolyzed polyacrylamide (PAM) can be bio-hydrolyzed on the amide side group, however, solid evidence regarding the biological cleavage of its main carbon chain backbone is limited. In this study, viscometry, flow field-flow fractionation multi-angle light scattering (FFF-MALS), and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) analysis were used to investigate the biodegradability of PAM with a nominal molecular weight of 2 × 10 7  Da (Da) in two suspended aerobic (25 and 40 °C) and two upflow anaerobic blanket reactors (35 and 55 °C) operated for 470 d under a hydraulic residence time (HRT) of 2 d. Both anaerobic and aerobic biological treatment reduced the viscosity from 2.02 cp in the influent to 1.45–1.60 cp, and reduced the molecular weight of PAM using FFF-MALS from 2.17 × 10 7  Da to less than one-third its original size. The removals of both the amide group and carbon chain backbone in the PAM molecule were further supported by the FTIR analysis. In comparison with the other conditions, thermophilic anaerobic treatment exhibited higher efficiency for PAM biodegradation. Batch test excluded the influence of temperature on the molecular weight of PAM over the range 25–55 °C, suggesting that cleavage of the main carbon chain backbone was attributed to biological degradation. Our results suggested that high molecular weight PAM was biodegradable, but mineralization did not occur. Graphical abstract: Highlights: PAM over 2 × 10 7  Da was reduced to less than one-third of its original size after biological treatment. Both aerobic and anaerobic treatment were effective in the hydrolysis of large molecular weight PAM. Thermophilic anaerobic treatment was more efficient in degrading PAM.